2019
DOI: 10.2478/rjim-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness in chronic hepatitis C virus infection

Abstract: Introduction. The severity of liver fibrosis can be assessed noninvasively today by liver stiffness measurements. Vibration-controlled transient elastography, shear wave elastography or magnetic resonance elastography are techniques increasingly used for this purpose. Methods. This article presents the recent advances in the use of new techniques for liver fibrosis assessment in chronic hepatitis C: the correlation between liver stiffness values and liver fibrosis estimated by liver biopsies, the prognosis rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The immune system response to cancer has proven to be of extreme importance and is indeed one of the most promising arms of treatment in the current panorama, with the development of immunotherapy for cancer treatment. Moreover, pathological conditions such as infection or cancer cause a change in the stiffness of tissues [ 134 , 135 ], affecting the immune response. In recent years, it has been shown that mechanosensitive ion channels play essential roles in the immune system and that they are important for proliferation [ 136 ], activation [ 136 , 137 ], migration [ 138 ] and cytokine production [ 137 ] of immune cells.…”
Section: Mechanosensation Of the Immune System And Immune Response To...mentioning
confidence: 99%
“…The immune system response to cancer has proven to be of extreme importance and is indeed one of the most promising arms of treatment in the current panorama, with the development of immunotherapy for cancer treatment. Moreover, pathological conditions such as infection or cancer cause a change in the stiffness of tissues [ 134 , 135 ], affecting the immune response. In recent years, it has been shown that mechanosensitive ion channels play essential roles in the immune system and that they are important for proliferation [ 136 ], activation [ 136 , 137 ], migration [ 138 ] and cytokine production [ 137 ] of immune cells.…”
Section: Mechanosensation Of the Immune System And Immune Response To...mentioning
confidence: 99%